Implementasi Pendekatan Behaviorisme Dalam Pemberian Reward Untuk Membentuk Karakter Disiplin Anak Usia Dini - Puspita, Yenda; Fitriana, Fitriana; Akhyar, Yundri (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Problems that occur when the child's attitude and behavior are not disciplined towards the character when carrying out activities. This is determined by methods or aspects of development that are not yet optimal, there are still children who do not have a disciplined character such as not applying attitudes when entering the toilet, fighting over toys with friends. This article aims to find out the behaviorism approach in reward prizes to shape the disciplined character of early childhood. Using the reward method to shape the character of discipline in children means the perfect way to give way or bridge disciplined students. The method used in this research is descriptive qualitative research method, descriptive method already exists a method that describes any conditions or symptoms that are in accordance with the events that occur in the field when the research is carried out. Descriptive method is research that provides a systematic, actual, and accurate description. about the news and the correlation between the phenomena studied. The results of the study found that using the behaviorism approach to rewards can produce disciplined character in early childhood. because it is very influential on various aspects of development, especially for learning to be responsible for using what is done, can control themselves and can motivate children to do the activity themselves